Comment on “Dirac fermions in Som–Raychaudhuri space-time with scalar and vector potential and the energy momentum distributions [Eur. Phys. J. C (2019) 79:541]” - Jirón Vicente, Andrés Giuseppe (2020)
Extraído del primer párrafo del documento: In a recent paper in this Journal, Sedaghatnia et al. have studied the Dirac equation in the presence of scalar and vector potentials in a class of flat Gödel-type space-times called Som–Raychaudhuri space-times by using the methods quasiexactly solvable (QES) differential equations and the Nikiforov Uvarov (NU) form. To achieve their goal, the authors have mapped the system into second-order differential equation Schrödinger-like problem). It is worthwhile to mention that the expressions obtained [Eqs. (2.8)–(2.17)] in Ref. [1] are correct. On the other hand, the second-order differential equation in Ref. [1] is wrong, probably due to erroneous calculations in the manipulation of the two coupled first-order differential equations. This fact jeopardizes the results of [1]. The purpose of this comment is to calculate the correct differential equation and following the appropriate procedure to obtain the solution for this problem.